Gene expression profiling reveals a lingering effect of prenatal alcohol exposure on inflammatory-related genes during adolescence and adulthood. (September 2020) - Gano, Anny; Prestia, Laura; Middleton, Frank A.; Youngentob, Steven L.; Ignacio, Cherry; Deak, Terrence
Graphical abstract: Highlights: PAE decreased immune-related gene expression in adolescence. PAE increased immune-related gene expression in adulthood. PAE induces long-lasting immune change in the olfactory bulb. Chronic prenatal alcohol altered baseline neuroimmune genes in the olfactory bulb. Abstract: Prenatal Alcohol Exposure (PAE) exerts devastating effects on the Central Nervous System (CNS), which vary as a function of both ethanol load and gestational age of exposure. A growing body of evidence suggests that alcohol exposure profoundly impacts a wide range of cytokines and other inflammation-related genes in the CNS. The olfactory system serves as a critical interface between infectious/inflammatory signals and other aspects of CNS function, and demonstrates long-lasting plasticity in response to alcohol exposure. We therefore utilized transcriptome profiling to identify gene expression patterns for immune-related gene families in the olfactory bulb of Long Evans rats. Pregnant dams received either an ad libitum liquid diet containing 35% daily calories from ethanol (ET), a pair-fed diet (PF) matched for caloric content, or free choice (FCL) access to the liquid diet and water from Gestational Day (GD) 11–20. Offspring were fostered to dams fed the FCL diet, weaned on P21, and then housed with same-sex littermates until mid-adolescence (P40) or young adulthood (P90). At the target ages of P40 or P90, offspring were euthanized via brief CO2 exposure and brains/blood were collected. Gene expression analysis was performed using a Rat Gene 1.0 ST Array (Affymetrix), and preliminary analyses focused on two moderately overlapping gene clusters, including all immune-related genes and those related to neuroinflammation. A total of 146 genes were significantly affected by prenatal Diet condition, whereas the factor of Age (P40 vs P90) revealed 998 genes significantly changed, and the interaction between Diet and Age yielded 162 significant genes. From this dataset, we applied a threshold of 1.3-fold change (30% increase or decrease in expression) for inclusion in later analyses. Findings indicated that in adolescents, few genes were altered by PAE, whereas adults displayed an increase of a wide range of gene upregulation as a result of PAE. Pathway analysis predicted an increase in Nf-κB activation in adolescence and a decrease in adulthood due to prenatal ethanol exposure, indicating age-specific and long-lasting alterations to immune signaling. These data may provide important insight into the relationship between immune-related signaling cascades and long-term changes in olfactory bulb function after PAE.